Larval development of the crab Amphithrax hemphilli (Rathbun, 1892) (Decapoda, Brachyura, Mithracidae) described from laboratory-reared material - de Paiva Barros-Alves, Samara (2022)
The complete larval development of Amphithrax hemphilli was described, illustrated, and compared with that of the previously described larvae of the genus Mithrax sensu lato. Specimens of A. hemphilli were sampled from the northeastern Brazilian coast. The larval development of A. hemphilli consisted of two zoeal stages and one megalopa. Amphithrax hemphilli shows morphological features in all stages of larval development that differ from those observed in other species of Amphithrax, Mithrax, and Maguimithrax. In the first larval stage, A. hemphilli was the only species with two aesthetascs on the antennule and the coxal endite of the maxillule with five setae. In the second larval stage, A. hemphilli was distinguished from the other species of the genus Mithrax sensu lato by the presence of five setae on the basial endite of the maxilla and 26 setae in the scaphognathite of the maxilla. Finally, the megalopa stage of A. hemphilli is characterized by the number of aesthetascs on the three-segmented exopod of the antennule, the setation of both the endopod of the third maxilliped, and pleonites 1-6. Based on the results obtained in the present study, we verified that the more advanced the larval stage, the more distinct characteristics are observed among species of the genus Mithrax sensu lato, facilitating the identification of species through later larval stages.